2019
DOI: 10.3389/fmicb.2019.02778
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Mycobacterium tuberculosis Driven by Historical European Trade in the South Pacific

Abstract: Mycobacterium tuberculosis (Mtb) is a globally distributed bacterial pathogen whose population structure has largely been shaped by the activities of its obligate human host. Oceania was the last major global region to be reached by Europeans and is the last region for which the dispersal and evolution of Mtb remains largely unexplored. Here, we investigated the evolutionary history of the Euro-American L4.4 sublineage and its dispersal to the South Pacific. Using a phylodynamics approach and a dataset of 236 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 71 publications
(98 reference statements)
3
29
0
Order By: Relevance
“…Molecular dating showed that this clade was introduced at the time of arrival of European traders. The clade is also found in M. tuberculosis isolates from indigenous populations in Canada 29 . While WGS studies of M. tuberculosis complex have not yet been carried out among indigenous populations in other regions, high levels of Mycobacterial interspersed repeat units—variable number tandem repeat genotype similarity have also been reported from the Warao in Venezuela 30 .…”
Section: Discussionmentioning
confidence: 88%
“…Molecular dating showed that this clade was introduced at the time of arrival of European traders. The clade is also found in M. tuberculosis isolates from indigenous populations in Canada 29 . While WGS studies of M. tuberculosis complex have not yet been carried out among indigenous populations in other regions, high levels of Mycobacterial interspersed repeat units—variable number tandem repeat genotype similarity have also been reported from the Warao in Venezuela 30 .…”
Section: Discussionmentioning
confidence: 88%
“…In fact, some of these repeated sequences have sufficient variation to characterize them based on reads. The boom of Whole Genome Sequencing provides plenty of data to dig into for evolutionary studies and changes the way drug-susceptibility testing will be done in the future [6,7]. We will show in the case of CRIS PR sequences how this diversity can reveal unexpected evolutionary patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However we should be cautious in our dating estimation. Indeed, we based this estimate on L4 mutations rates [96]; we know that calibration of the molecular clock varies a lot according to samples, time-frames and lineages (between 0.04 to 2.2 SNPs per-genome-peryear) [100]. Dating can be comforted if adequate correlation exists between historical, genomic, epidemiological and demographic facts.…”
Section: Discussionmentioning
confidence: 99%